Niche overlapping in Hypopachus (Anura: Microhylidae) and new record of Hypopachus variolosus in Central Mexico - Gómez-Benitez, Aldo (2026)
Introduction: Microhylidae is one of the most diverse anuran families. The Hypopachus genus comprises a group of relatively unknown fossorial frogs distributed from the United States to Panama. To date, their environmental requirements and niche overlap among species remain unstudied. Objectives: To assess niche overlap among four Sheep Frog species, genus Hypopachus, and report a sighting of Hypopachus variolosus in the State of Mexico after 66 years with no records. Methods: We conducted fieldwork in Tonatico, State of Mexico, Mexico. The vegetation consists of low deciduous forest under a semi-warm subhumid climate. We modeled the environmental occupation of H. variolosus, H. ustus, H. barberi, and H. pictiventris through a principal component analysis and kernel density estimation, calculated niche overlap using Schoener’s D metric, and modeled the environmental suitability of each species using the maximum entropy algorithm. Results: On 25 October 2024, we captured a male H. variolosus measuring 25.4 mm. A significant niche overlap was detected only between H. variolosus and H. ustus. Preference for low temperatures distinguishes H. barberi from the other species, while preference for high precipitation regimes sets H. pictiventris apart. H. variolosus has the broadest distribution range, occurring from Texas to western Panama, followed by H. ustus, which ranges from the coasts of the Gulf of Mexico and the Pacific in Mexico to Nicaragua. H. barberi is distributed from the state of Chiapas, Mexico, to northern Nicaragua. The most range-restricted species is H. pictiventris, found from southeastern Nicaragua to western Panama. Conclusions: Our results suggest that meso- and microclimatic variables may play a key role in reducing competition among sympatric Hypopachus species. Additionally, the conditions of high temperatures and low rainfall that prevail in Mexico and Central America, favor the extensive distribution of H. variolosus and H. ustus.